A snapshot of the global policies and practices of medicine use reviews by community pharmacist in chronic diseases: a narrative review - Mubarak, Naeem; Raja, Sarwat Ali; Mehmood Khan, Tahir; Zin, Che Suraya (Pakistan Medical Association, 2021)
Medicine use review is a tool to improve medication adherence and safety. Current narrative review was planned to explore global policies and practices of medicine use review by community pharmacists in chronic diseases and its impact and way forward for low- and middle-income countries. Key words, such as ″medicine use review″, ″medication therapy management″ and ″community pharmacy″ were used for search on PubMed and CINAHL databases for articles published from 2004 to 2019. Medicine use review has opened an avenue of ongoing collaboration between community pharmacists and general practitioners. High-income countries have witnessed a gradual yet cautious adoption of these services through eﬀective policy shift. In terms of practices and impact, the situation in high-income countries was promising where on an average ″type-II″ medicine use review was widely in practice and had improved clinical, humanistic and economic outcomes in chronic disease. However, in low- and middle-income countries, a paucity of eﬀective policies was noted. Nevertheless, an emergent recognition of the potential of community pharmacists to contribute to the management of chronic diseases was evident